Democratic Functions of Civil Society - Basilashvili, Natela (European Journal of Life Safety and Stability (2660-9630), 2022)
Normal conditions for the existence and functioning of civil society are created by a democratic government. Here, it is legitimate because the law not only prohibits but also protects it. It is true that the government does not create or interfere in the activities of civil society organizations, but it does form the legal framework within which they operate independently and freely. The government does not govern but regulate the activities of civil society. The basis for this regulation is the Constitution and other relevant legislative acts. One of the important tasks of civil society is to control the activities of the government. The government often oversteps its authority, resulting in the abuse of power. He makes full use of his rights but pays little attention to fulfilling his obligations. It is forgotten that in addition to rights, it also has obligations. For example, the government is obliged to protect human rights, but often violates them itself. He is also obliged to uphold the rule of law, but he himself commits lawlessness, he must fight corruption, but many bribe-takers work in his structures. Civil society cannot interfere in the activities of the government. He cannot assume the function of government. He has no right to issue laws, to enforce them in life, and to administer justice. But civil society has the right to expose violations of human rights and the rule of law, violation of the freedom and dignity of the individual by the authorities.